Ergonomic Evaluation of Improved Grain Cleaning Technologies - Comparative Study of Traditional and Improved Tools (Indian Journal of Extension Education, 2014)
This study was conducted to assess ergonomically the efficiency of improved hanging type cleaner grader. Twenty farmwomen were selected to assess and compare the impact of improved technologies over one. The physiological cost of work and energy expenditure in terms of heart rate cardiac cost, time required, strokes, output were observed to be lower while performing selected activities with the improved technologies compared to the traditional one. The work output was also found higher with all of the improved technologies. The activity was performed with both the traditional method using as well as by using supa the improved tools. Results of the study showed that the average heart rate and energy expenditure of the women were reduced significantly while performing the grain cleaning activity with the use of improved toll manufactured by CIAE, Bhopal. The use of both the improved tools also leads to reduction in the muscular stresses. Further it was observed that work productivity with the improved tool Hanging sieve had significantly improved. It was therefore recommended that women should be motivated to use the improved tools for grain cleaning to minimize their health hazards.